2009
DOI: 10.1038/onc.2009.435
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin inhibits oncogenic intestinal ion channels and neoplasia in APCMin/+ mice

Abstract: The adenomatous polyposis coli (APC) gene is mutated in familial adenomatous polyposis. Mice with a heterozygous APC Min mutation develop multiple intestinal neoplasia (Min) leading to premature death. Early in colorectal carcinogenesis, APC Min/ þ mice show enhanced Akt-mammalian target of rapamycin (mTOR) signaling, which is paralleled by upregulation of oncogenic K þ channels. In this study, we tested the effect of mTOR inhibition with rapamycin on tumor formation in APC Min/ þ mice and evaluated ion channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 32 publications
4
39
0
Order By: Relevance
“…It was suggested that increased ENaC-mediated salt absorption would lead to decreased hydration of the colonic contents, thus leading to constipation, which has been proposed as a precipitating factor in the development of colonic carcinoma (89,359). The increased ENaC expression and sodium absorption in this mouse were rescued by treatment with rapamycin, consistent with previous reports in lung epithelia and with the recently described role of mammalian target of rapamycin to increase ENaC currents via phosphorylation of SGK1 (227,257,290).…”
Section: Asics Enacs and Cancersupporting
confidence: 79%
“…It was suggested that increased ENaC-mediated salt absorption would lead to decreased hydration of the colonic contents, thus leading to constipation, which has been proposed as a precipitating factor in the development of colonic carcinoma (89,359). The increased ENaC expression and sodium absorption in this mouse were rescued by treatment with rapamycin, consistent with previous reports in lung epithelia and with the recently described role of mammalian target of rapamycin to increase ENaC currents via phosphorylation of SGK1 (227,257,290).…”
Section: Asics Enacs and Cancersupporting
confidence: 79%
“…As GSK-3 suppresses both Wnt and mTOR pathways (2,14), our demonstration that APC enhances GSK-3 activity provides a mechanistic link between APC loss of function and activation of these two downstream signaling pathways. In support of this mechanism, tumor formation in mice with similar APC mutations is blocked by mTOR inhibitors (54,55). Furthermore, bladder-specific ␤-catenin stabilization synergizes with PTEN deletion, which activates mTOR, to promote bladder cancer in mice (56).…”
Section: Discussionmentioning
confidence: 91%
“…Notably, the mTOR-inhibitor rapamycin increased Ano1 expression in both proximal and distal colon (figure 4d). This inverse correlation between low Ano1 levels and upregulation of mTOR [51] suggests that Ano1 may be inhibitory on proliferation of mouse intestinal epithelial cells, similar to HT 29 cells. Interestingly, a fast growing subclone of T 84 colonic epithelial cells (T 84 fast) is lacking expression of Ano1, when compared with the slowly growing parental cells (T 84 slow) [28] ( figure 5a,b).…”
Section: Ano1 Required For Terminal Differentiation?mentioning
confidence: 97%